Exploring a Structural Model of Teaching Enjoyment, Teacher Self-Efficacy, and Work Engagement - Xiao, Yan; Fathi, Jalil; Mohammaddokht, Farnoosh (Frontiers in Psychology, 2022)
Due to the complexity of teaching, determining the variables influencing teachers’ work engagement is a rewarding research area. In line with this research agenda, the purpose of this study was to test a structural model of work engagement based on teacher self-efficacy and teaching enjoyment among English as a Foreign Language (EFL) teachers. For this purpose, 315 Iranian English instructors completed an online survey. Initially, the measurement models for the three latent variables were averred via conducting Confirmatory Factor Analysis (CFA). Following that, Structural Equation Modeling (SEM) was utilized to test the hypothesized model. SEM results showed that both self-efficacy and teaching enjoyment were the significant predictors of teachers’ work engagement, although teacher self-efficacy was a stronger predictor than teaching enjoyment. The findings might have notable implications for English teachers.